Hydrogen production by crude glycerol steam reforming over Ni-La-Ti mixed oxide catalysts, - Veiga, Santiago (2017)
The production of H2-rich gaseous mixtures from steam reforming of crude glycerol was investigated on ternary Ni-Le-Ti catalysts. Ni-La-Ti mixed oxides containing 15 wt% of Ni and a La/Ti atomic ratio of 1 were prepared by a coprecipitation method and characterized by a variety of physical and spectroscopic techniques. Samples were calcined in air at 700 ºC or 850 ºC for 2 h. Ni-La-Ti samples calcined at 700 ºC (NiLaTi700) showed a well definedNiO phase and an amorphous La-Ti mixed oxide, while those calcined at 850 ºC(NiLaTi850), exhibited two well defined phases of NiO and LaTiO3 perovskite, respectively. NiO was completely reduced to metallic Ni on both solids under pure H2 at 650 ºC and the resulting Ni0 phase remained as a separate phase under the steam reforming conditions. Standard catalytic tests for the steam reforming of glycerol were performed at 500 ºC or 650 ºC by feeding the fixed-bed tubular reactor with a crude glycerol:water solution containing 30 wt% glycerol. The best results were achieved on NiLaTi700 at 650 ºC, obtaining H2 yields and H2/CO2 molar ratios close to the theoretical values predicted by the steamreforming reaction stoichiometry. A slight activity decay was observed on NiLaTi700 with the progress of the reaction, probably reflecting the formation of small amounts of coke.